2013
DOI: 10.1108/02644401311314376
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and fatigue caused by pressure pulsations originating in the vaneless space for a Kaplan turbine with high head

Abstract: Purpose -Hydraulic instabilities are one of the most important reasons causing vibrations and fatigues in hydraulic turbines. The present paper aims to find the relationship between pressure pulsations and fatigues of key parts of a Kaplan turbine. Design/methodology/approach -3D unsteady numerical simulations were preformed for a number of operating conditions at high heads for a prototype Kaplan turbine, with the numerical results verified by online monitoring data. The contact method and the weak fluid-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…They found that the stress caused by hydraulic force is one of the main reasons of the runner fatigue failures and cracks. In terms of the other essential components of pump turbines, Luo et al [32][33][34] focused on the stress of the rotor bracket of the generator and the piston rod of the blade. Improvements in design are made based on stress analyses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the stress caused by hydraulic force is one of the main reasons of the runner fatigue failures and cracks. In terms of the other essential components of pump turbines, Luo et al [32][33][34] focused on the stress of the rotor bracket of the generator and the piston rod of the blade. Improvements in design are made based on stress analyses.…”
Section: Introductionmentioning
confidence: 99%
“…5 They may run of-river without a significant water storage, 6 but their hydraulic efficiency is not high compared to large Kaplan turbines added to water feeding not stable. Kaplan turbines have a rather large vaneless space inducing a complex dissipation of vanes' wakes and vortices, causing large pressure pulsations, 7 added to the flow rotation and secondary flows near the hub and shroud, which are difficult to capture. 8 The energy transfer is accompanied by pressure oscillations caused by vortices, cavitations, and complex unsteady flow phenomena inducing excessive blade vibration.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, all components of the hydraulic excitation force frequencies are included by using the pressure loads on the runner surfaces obtained from unsteady flow simulation as boundary condition for the dynamic stress analysis. However, the early attempts did not take into account the fluid added mass (Zhou et al, 2007;Wang et al, 2013;Luo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%